The Making of a Philippine province Romblon during the American Colonial Period. - Esquejo, Kristoffer R. (2014)
This paper discusses the political transformation of Romblon in the Central Philippines during the American colonial era. Its status as a province underwent a series of changes that arose from the strategies of two local politicians, Francisco P. Sanz and Leonardo F. Festin, with the assistance of two national political figures. Romblon was first established as an independent province by the Taft Commission in1901. Six years later, it was abolished and annexed to Capiz, its former mother province during the Spanish era. This first abolition was a result of Dean C. Worcester’s intervention to appoint Sanz as governor
and restore the political fortunes of the latter, who had lost an election. In 1918, Romblon again became a separate province through the initiative of Festin, who, ironically, would be responsible for its later demotion into an experimental province in 1940. For more than twodecades, Festin dominated local politics as the Representative to the Philippine Legislature, while his patron and party head Manuel L. Quezon, who later became President of the Philippine Commonwealth, monopolized power at the national level.
Keywords: Romblon